Particle sorting by Paramecium cilia arrays - Mayne, Richard; Whiting, James G.H.; Wheway, Gabrielle; Melhuish, Chris; Adamatzky, Andrew (BioSystems, 2017)
Motile cilia are cell-surface organelles whose purposes, in ciliated protists and certain ciliated metazoan epithelia, include generating fluid flow, sensing and substance uptake. Certain properties of cilia arrays, such as beating synchronisation and manipulation of external proximate particulate matter, are considered emergent, but remain incompletely characterised despite these phenomena having being the subject of extensive modelling. This study constitutes a laboratory experimental characterisation of one of the emergent properties of motile cilia: manipulation of adjacent particulates. The work demonstrates through automated videomicrographic particle tracking that interactions between microparticles and somatic cilia arrays of the ciliated model organism Paramecium caudatum constitute a form of rudimentary ‘sorting’. Small particles are drawn into the organism's proximity by cilia-induced fluid currents at all times, whereas larger particles may be held immobile at a distance from the cell margin when the cell generates characteristic feeding currents in the surrounding media. These findings can contribute to the design and fabrication of biomimetic cilia, with potential applications to the study of ciliopathies.